2017
DOI: 10.16923/reb.v15i0.702
|View full text |Cite
|
Sign up to set email alerts
|

“METABOLIC RIDE” a conceptual evaluation tool for metabolic biochemistry teaching for graduate and postgraduate students in biological sciences and related areas

Abstract: Biochemistry as a discipline have a high degree of difficulty. Otherwise, application of creative games as teaching methodology has spread in various disciplines. "METABOLIC RIDE" board game is a conceptual and perceptual ResumoA disciplina de bioquímica no geral é considerada de alto grau de dificuldade. Contudo, a aplicação de jogos lúdicos como metodologia de ensino vem se disseminando em várias disciplinas. "METABOLIC RIDE" é uma ferramenta de avaliação conceitual e de percepção para o ensino de bioquímica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In particular, Postgraduates increased unemployment in the long run, which partly agrees with results from a prior study by Bakkabulindi, (2006), who found higher education in general to cause unemployment in Uganda. These findings could stem from the fact that they have difficulty in obtaining employment (Townsend, & Brookins, 2016;Ermini, Papi, & Scaturro, 2017;Gaeta et al, 2017). This finding aligns 116 ISSN 1927-6044 E-ISSN 1927 to the argument that there are few employers postgraduates, especially Doctorate holders (McCarthy& Wienk, 2019), especially for the labour markets in developing countries, with little appreciation and demand for research.…”
Section: Discussion and Policy Recommendationsmentioning
confidence: 79%
See 1 more Smart Citation
“…In particular, Postgraduates increased unemployment in the long run, which partly agrees with results from a prior study by Bakkabulindi, (2006), who found higher education in general to cause unemployment in Uganda. These findings could stem from the fact that they have difficulty in obtaining employment (Townsend, & Brookins, 2016;Ermini, Papi, & Scaturro, 2017;Gaeta et al, 2017). This finding aligns 116 ISSN 1927-6044 E-ISSN 1927 to the argument that there are few employers postgraduates, especially Doctorate holders (McCarthy& Wienk, 2019), especially for the labour markets in developing countries, with little appreciation and demand for research.…”
Section: Discussion and Policy Recommendationsmentioning
confidence: 79%
“…The question is whether this applies to both undergraduates and post graduates. In some places postgraduates especially doctorates, although employed, have found it difficult to come by appropriate employment (Townsend, & Brookins, 2016;Ermini, Papi, & Scaturro, 2017;Gaeta et al, 2017) as many non-academic employers have a little yearning and appreciation for research. Post graduate employability has further been devalued by assumed lower quality as a result of cram-work, and higher cost of employing postgraduates, that does not give justification for employing postgraduates in developing countries (Zhou, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%